Hegel’s Critique of Sense-certainty and its Rehabilitation by Feuerbach from the Perspective of the Theory of Photography (Revista Eletrônica Estudos Hegelianos, 2024)
Feuerbach proposes a break with modern philosophy through his critique of Hegelian speculation. Aiming for a new materialist philosophy, he conceptualizes sense and immediate intuition as the primary organ of reality. The article examines Feuerbach’s re-evaluation of Hegel’s critique of sense-certainty and his rehabilitation of this figure of consciousness. His rehabilitation is contextualized within the cultural-media revolution of photography, suggesting that this approach responds to the impact of the new media techniques of the time. According to the author, sense-certainty should be understood as a “theoretical reflection of a figure of the spirit of the people based on a media technique.” Therefore, it shows that photography, as a new technical medium, plays a central role in Feuerbach’s rehabilitation of sense and immediate certainty. The analysis reveals that the discussion on this figure of consciousness goes beyond the philosophical debate, as it reflects a significant change in the way experience and reality are organized and understood.